THE DETERMINANTS OF E-BUDGETING IMPLEMENTATION IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Bambang Subiyanto; Syamsudin; Khairul Saleh L. Tobing; Kumba Digdowiseiso; Norakma Abd Majid (PT. Radja Intercontinental Publishing, 2023)
This study conducts a comprehensive analysis of the factors that influence the implementation of E-Budgeting in Indonesia. Furthermore, the research highlights the significance of modernization in the management of public budgets and the government's endeavors to enhance efficiency and transparency by adopting E-Budgeting. The primary goal is to ascertain the pivotal factors that impact the effective execution of this system. The employed approach is Systematic Literature Review, which consolidates findings from diverse reputable sources. The research findings and analysis indicate that the factors influencing the implementation of E-Budgeting encompass a range of technical, political, social, and cultural determinants. The primary factors that influence implementation are resources, political backing, inter-agency coordination, and adherence to regulations. Furthermore, organizational culture, institutional capacity, stakeholder participation, and ongoing evaluation also exert significant influence. Implementing E-Budgeting has the effect of enhancing efficiency, transparency, and accountability in the management of public budgets. The research concludes that the adoption of E-Budgeting in Indonesia represents a favorable stride towards enhanced efficiency and transparency in budget administration. However, in order to attain complete success, it is imperative to give significant consideration to the determinant factors that have been mentioned. Implementing E-Budgeting in Indonesia can yield significant advantages in promoting sustainable economic growth and enhancing governance by effectively addressing these challenges.